Complement pathway: Risk molecular pattern of cardiovascular diseases in patients with diabetic nephropathy - Liu JunFei; Qian XiaoPing; Wang TaoXia; Liu XiaoLi; Liu WeiGang; Wang LiJie; Zhang HuiFang; Han Li; Li GuiYing; Yu XiaoJuan (Journal of Medical Biochemistry)
Background: Among individuals with diabetes mellitus, diabetic nephropathy (DN) is a common microvascular complication. As renal dysfunction progresses in DN patients, the risk of cardiovascular disease (CVD) significantly increases. The current effective treatment of DN and CVD demands identifying and managing their risk factors. Methods: Patients diagnosed with DN from October 2022 to October 2023 were selected for cross-sectional study and divided into DN group (n=58) and DN/CVD group (n=40) based on the presence of CVD. Univariate analysis was conducted using clinical data, and statistically significant independent variables were analysed through multivariate Logistic regression to identify independent factors influencing CVD in DN patients. A regression model was developed to examine the non-linear relationship between C1q, UA, CRP, and the risk of CVD. The receiver operating characteristic curve was used to analyse the predictive efficacy of the indicators. Results: When elevated, UA and C1q were independent factors for CVD. A linear relationship existed between UA and C1q and the risk of CVD in DN patients. C1q showed better predictive performance. Conclusions: As UA and C1q levels rise, the risk of CVD in DN patients significantly increases. In DN patients, UA and C1q are associated with CVD development and progression, offering some supportive evaluation value for the patient's condition.